IMPLEMENTASI PROGRAM PENCEGAHAN PENYALAHGUNAAN NARKOBA OLEH BNN KOTA PONTIANAK PADA SISWA SMAN 2 KOTA PONTIANAK - Meli Udana E.21111105 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The problem of drug abuse in the city of Pontianak, especially on a student needs to be taken seriously by some of the prevention of drug abuse is due to the danger of bad things always lead to human misery is prolonged even a potential threat to the future generation. The successful implementation of drug abuse prevention programs can not be separated from the role of all levels of society and government in support of drug abuse prevention programs are encouraged BNN Pontianak city. The fact is there are still obstacles to the implementation of drug abuse prevention programs in both the implementation and the factors that become bottlenecks. The focus of this article is the implementation of drug abuse prevention programs by BNN Pontianak in Pontianak SMAN 2. This study aims to portray the implementation of drug abuse prevention programs by BNN Pontianak in Pontianak SMAN 2. The results of this study covers four things: drug abuse prevention program in the form of information dissemination program consisting of counseling, socialization and a cadre of anti drug, instructions and procedures performed in 2010 by Presidential Decree Nomor.23 on BNN, rule head  BNN  and refer to the number. 3 and 4 of 2010 concerning the organization and functioning of BNN, the goals and objectives of this program is that the students have the mindset, attitudes, and skilled reject abuse and illicit drug trafficking activities within the school and program scheduling is done by planning in 1 month years. Suggestions author on drug abuse prevention program implementation is to be evaluated more thoroughly the aspects that are less effective, and less than optimal in favor and support the success of this program.Keywords : Implementation ,Prevention Programs, Drug , Student, National Narcotics Agency.